2014
DOI: 10.4181/rnc.2013.21.870.4p
|View full text |Cite
|
Sign up to set email alerts
|

Aplicabilidade Clínica da Variabilidade da Frequência Cardíaca

Abstract: Rev Neurocienc 2013;21(4):600-603 revisão 600 RESUMOObjetivo. O objetivo deste trabalho foi revisar aspectos conceituais da Variabilidade da Frequência Cardíaca (VFC), seus dispositivos de mensuração, índices utilizados para sua análise e utilização clínica. Método. Uma revisão de literatura não sistemática realizada através de busca eletrônica conduzidas nas seguintes bases de dados: Medline/ PubMed, Lilacs, Ovid, Science Direct e Biomed Central acerca da utilização clínica da VFC. Resultados. A VFC compreend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…26 An increase or reduction in HRV indicates a change in the sympathetic-vagal balance in which a high HRV indicates proper functioning of autonomic control. 12,[26][27][28] In this study, no statistically significant intergroup differences in SDNN and RMSSD were identified during rest or in the acute response to the 1RM test despite lower expected autonomic modulation rates in the normotensive condition compared to the prehypertensive condition. In contrast, Paschoa et al (2006) reported a reduction in the SDNN and RMSSD indices in normotensive individuals after strength exercises.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…26 An increase or reduction in HRV indicates a change in the sympathetic-vagal balance in which a high HRV indicates proper functioning of autonomic control. 12,[26][27][28] In this study, no statistically significant intergroup differences in SDNN and RMSSD were identified during rest or in the acute response to the 1RM test despite lower expected autonomic modulation rates in the normotensive condition compared to the prehypertensive condition. In contrast, Paschoa et al (2006) reported a reduction in the SDNN and RMSSD indices in normotensive individuals after strength exercises.…”
Section: Discussionmentioning
confidence: 82%
“…28 In the frequency domain, in which there is a real possibility of demonstrating the sympathetic-vagal balance on the heart, a difference during rest in LF/HF rest the variable LF/HF was identified with a predominance of the sympathetic system in the PH group, consistent with findings of published reports. 12,27,28 No difference was observed in the behavior of the variable LF/HF after the adjustment of HRV to body fat indices. [26][27][28][29] However, the relationship between obesity and autonomic dysfunction seems dependent on the obesity indicator used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diversas causas podem ser responsáveis por alterar a FC na população pediátrica, incluindo cardiopatias, prematuridade e patologias neurológicas [3,4]. Isso pode levar a redução da capacidade de consumo máximo de oxigênio, podendo desencadear dispneia compelida pelo exercício, impactando negativamente na sua qualidade de vida [5,6].…”
Section: Introductionunclassified